1991
DOI: 10.1063/1.460650
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic electronic interactions in the ion-pair states of NeICl

Abstract: Nonadiabatic interactions in the NeICl van der Waals complex have been explored in the lowest energy triad of ICl ion-pair states (∼39 000 cm−1). Dispersed fluorescence measurements reveal emission characteristic of multiple ion-pair electronic states, with the relative contributions from the E(0+), β(1), and D′(2) states changing with the initial ICl vibrational excitation (vICl). Emission directly from NeICl (vICl=0) complexes indicates that the initially prepared NeICl levels have mixed electronic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…21 In turn, the value for the near T-shaped Ne-ICl binding energy is larger than an early experimental estimation 33 but in good accord with later reported experimental values. 34,36 For the Rg-ICl complexes studied, the present surfaces are the first ab initio ones available and the comparison with experimental data demonstrates the high quality of them. Using these CCSD͑T͒ surfaces, work is in progress to study the dynamics and spectra of the He-ICl and Ne-ICl complexes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…21 In turn, the value for the near T-shaped Ne-ICl binding energy is larger than an early experimental estimation 33 but in good accord with later reported experimental values. 34,36 For the Rg-ICl complexes studied, the present surfaces are the first ab initio ones available and the comparison with experimental data demonstrates the high quality of them. Using these CCSD͑T͒ surfaces, work is in progress to study the dynamics and spectra of the He-ICl and Ne-ICl complexes.…”
Section: Discussionmentioning
confidence: 75%
“…This leads to larger values of dissociation energy of Ne-ICl in the A and X electronic states than the ones previously estimated. 33 Thus, a higher value of D 0 Ϸ60 cm Ϫ1 has been adopted 34,36 for the bond energy of Ne-ICl in A state, implying an upper value of D 0 ϭ70Ϯ5 cm Ϫ136 for the dissociation energy of the Ne-ICl ground state. The present CSSD͑T͒ result of D 0 ϭ65.2 cm Ϫ1 is consistent with this experimental estimate.…”
Section: B Vibrational Analysismentioning
confidence: 99%
“…12 No fluorescence signals were observed for transition energies above these features, which include the Ϸ45 cm −1 region between the Ne+ I 35 Cl͑E , v † =0͒ and the higher-lying Ne +I 35 Cl͑␤ , v † =0͒ dissociation limits. 12 No fluorescence signals were observed for transition energies above these features, which include the Ϸ45 cm −1 region between the Ne+ I 35 Cl͑E , v † =0͒ and the higher-lying Ne +I 35 Cl͑␤ , v † =0͒ dissociation limits.…”
Section: B He¯icl Binding Energiesmentioning
confidence: 98%
“…Stephenson et al 12 reported on the varying nonadiabatic electronic interactions in different intermolecular vibrational levels bound within the Ne+ I 35 Cl͑␤ , v † =0-4͒ potentials. These interactions were characterized by recording two- …”
Section: B He¯icl Binding Energiesmentioning
confidence: 99%
See 1 more Smart Citation